An Interpretive Review of Psychoanalytic Literature on Empathy in the Therapeutic Relationship - Kistasamy, Kumeshni (Auckland University of Technology, 2017)
This dissertation is an interpretive review of psychoanalytic literature on empathy within the therapeutic relationship. The creative science of hermeneutics is used to explore the history of empathy and its function within the therapeutic relationship. A critical analysis of the literature provides the platform for assessing present arguments for the importance of empathy in the therapy relationship. This analysis identified three important areas neglected in the research. These are the wider context of the evolution of empathy, the role of culture and consideration of the client's experience. A discussion of these areas concludes this dissertation.